(untitled) (Research, Society and Development, 2022)
In January 2020, the World Health Organization declared the COVID-19 outbreak a global health emergency. The present study aimed to identify the influence of the COVID-19 pandemic on the mental health of undergraduate dental students at the Federal University of Campina Grande. The study was cross-sectional, with an inductive approach and a comparative, statistical-descriptive procedure, adopting the WHOQOL-HIV BREF questionnaire, and the universe was composed of regularly enrolled students from the 1st to the 9th period. The largest participation in the research was from the fourth period (15.6%). Demographic data revealed a higher number of female students (60.3%), mixed race (48.7%), single marital status (94.2%), unemployed (93.8%) and with an income of up to two minimum wages (46.4%). Regarding quality of life, 33.9% of the sample classified it as good. 79.9% of the participants had some type of test to detect the virus and 46.9% tested positive. 51.3% of the sample did not feel unmotivated to perform their oral hygiene routine and (88.8%) did activities to distract themselves during this period. The results also pointed out that the consumption of alcoholic beverages was observed in (35.7%) of the sample and that (92.9%) did not use tobacco during this period. (16.1%) reported having their mental health little affected, (95.5%) felt anxiety sometimes, (80.8%) felt more stressed, and (36.2%) lost a relative or close person during the pandemic. From these results it will be possible to have a different look at mental health, enabling scientific knowledge about its psychosocial consequences.